A framework for clinical commissioning of 3D‐printed patient support or immobilization devices in photon radiotherapy. (8th July 2018) - Meyer, Tyler; Quirk, Sarah; D'Souza, Malgorzata; Spencer, David; Roumeliotis, Michael
Abstract: Purpose: The objective of this work is to outline a framework for dosimetric characterization that will comprehensively detail the clinical commissioning steps for 3D‐printed materials applied as patient support or immobilization devices in photon radiotherapy. The complex nature of 3D‐printed materials with application to patient‐specific configurations requires careful consideration. The framework presented is generalizable to any 3D‐printed object where the infill and shell combinations are unknown. Methods: A representative cylinder and wedge were used as test objects to characterize devices that may be printed of unknown, patient‐specific dimensions. A case study of a 3D‐printed CSI immobilization board was presented as an example of an object of known, but adaptable dimensions and proprietary material composition. A series of measurements were performed to characterize the material's kV radiologic properties, MV attenuation measurements and calculations, energy spectrum water equivalency, and surface dose measurements. These measurements complement the recommendations of the AAPM's TG176 to characterize the additional complexity of 3D‐printed materials for use in a clinical radiotherapy environment. Results: The dosimetric characterization of 3D‐printed test objects and a case study device informed the development of a step‐by‐step template that can easily be followed by clinicians to accurately and safely utilize 3D‐printed materials as patient‐specific support or immobilization devices. Conclusions: A series of steps is outlined to provide a formulaic approach to clinically commission 3D‐printed materials that may possess varying material composition, infill patterns, and patient‐specific dimensions.